Penyusunan Indeks Kerentanan Sosial Ekonomi Pekerja Perempuan terhadap Pandemi Covid-19 di Indonesia - Syaadah, Arini Alva; Sitorus, Jeffry R. H. (Seminar Nasional Official Statistics, 2023)
The emergence of the Covid-19 pandemic has had a negative impact on the vulnerability of women workers in Indonesia. In a pandemic situation, women workers are increasingly vulnerable in terms of continuing their working status, which has a negative impact on their social and economic conditions. The impact of the Covid-19 pandemic felt by women workers can lead to more complex problems if special attention is not given. A measure is needed that can show the socio-economic vulnerability of women workers to the Covid-19 pandemic in Indonesia. Therefore, this study aims to construct an Index of Socio-Economic Vulnerability of Women Workers to the Covid-19 Pandemic in Indonesia by analyzing data from the results of Survei Angkatan Kerja Nasional (Sakernas) in August 2021. The analytical method used in construction the index refers to the OECD guidelines using exploratory factor analysis. The results showed that there were 12 indicators in three factors, namely workers' rights, workers' social conditions, and workers' demographic-economic conditions. Based on the IKSEPP Covid-19 score, it was found that the province with the highest index score was NTB and the lowest was Kep.Riau.